TANTANGAN MODERASI BERAGAMA DALAM IMPLEMENTASI P5RA DI MADRASAH - ZAINUL MUFLIHIN (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
This study aims to analyze the implementation of religious moderation in madrasah through P5RA activities. This research uses a qualitative approach with a literature study method to identify challenges, obstacles, and substances related to the cultivation of religious moderation values in madrasas. The results showed that P5RA activities have great potential in instilling values of tolerance, peace and nationality in students. However, its implementation in madrasas is still constrained by several factors, such as the lack of readiness of facilities and infrastructure and the incomplete understanding of P5RA among educators. In addition, substantial challenges in instilling religious moderation in madrasas arise due to the spread of radicalism, differences in religious understanding among students, and the influence of globalization that brings in various ideologies that are not in line with religious moderation. Therefore, it is necessary to improve the understanding of P5RA, improve supporting facilities, and strengthen a more inclusive curriculum to achieve the goal of moderate and harmonious education in madrasas. This study provides recommendations for the development of more effective strategies in implementing religious moderation in madrasas in order to create a more tolerant and nationalistic-minded generation.